All-polymer stretchable fibrous solar cell and preparation method thereof
By adopting all-polymer acceptor systems and introducing elastic fibers and SEBS in fibrous solar cells, the problem of degradation in existing fibrous solar cells under high tensile strain is solved, and higher tensile performance and stability are achieved sex.
Patent Information
- Application Number
- CN202310985593.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-07
AI Technical Summary
The performance of existing fibrous solar cells is greatly reduced when the tensile strain exceeds 40%, and the mechanical properties of the small molecule acceptor system are insufficient, making it difficult to meet the needs of varying degrees of deformation in wearable devices.
Using a full polymer acceptor system, the mechanical tensile properties of the device are improved by introducing elastomeric fibers and elastomeric additives, such as SEBS, into the fibrous electrodes and light absorbing layers. The specific method includes using TPU as the elastic fiber and ITO as the electrode layer material, and adding 0-30 wt% SEBS to the light absorbing layer of the organic photovoltaic material.
Maintaining more than 80% photoelectric conversion performance under 60% tensile strain, and repeating more than 1,000 times under 30% tensile deformation can still maintain more than 80% initial efficiency, significantly improving the tensile performance and stability of the device sex.
Smart Images

Figure CN119451378A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photovoltaic devices, and in particular to an all-polymer stretchable fibrous solar cell and a preparation method thereof. Background Art
[0002] Flexible fiber-shaped organic solar cells (FOSCs) have the advantages of being safe, lightweight, flexible, and having an all-solid-state structure. They can not only generate electricity, but can also be integrated with clothes and textiles, showing great application potential in the field of wearable devices. In practical applications, fiber-shaped solar cells need to meet the basic requirements of high efficiency, flexibility, and wearability, and also need to be stretchable so that they can adapt to different degrees of deformation during wearing.
[0003] CN115513385A discloses a stretchable fibrous solar cell that can maintain 90% of its initial performance under a tensile strain of 30%. However, since small molecules usually exhibit brittleness, the mechanical properties of a blend system based on a polymer donor and a non-fullerene small molecule acceptor are usually insufficient. When the tensile strain exceeds 40%, its performance drops significantly. Therefore, there is still much room for improvement in the tensile performance of the device. Summary of the invention
[0004] On the basis of previous studies, the inventors of the present invention found that, compared with small molecule receptors, polymer receptors can not only maintain similar photoelectric properties as small molecule receptors, but also have better mechanical tensile properties, and completed the present invention on this basis.
[0005] An object of the present invention is to provide an all-polymer stretchable fiber-shaped solar cell, the cell comprising:
[0006] A fibrous stretchable electrode, comprising an elastic fiber and an electrode layer coated on the elastic fiber; wherein the elastic fiber is made of a material selected from TPU, SBS, SEBS, SIS, PDMS, EPDM, POE, TPE, TPV, TPE, PPE and TREE, and the electrode layer is made of a material selected from ITO, Ag NPs, Ag NWs, Au NPs, Au NWs, Cu NWs, Cu NPs, Cu NWs, carbon nanotubes, graphene, carbon nanosheets and PEDOT:PSS; preferably, the elastic fiber is made of TPU, and the electrode layer is made of ITO;
[0007] An electron transport layer, which is coated on the outside of the fibrous inner layer stretchable electrode and is made of a material selected from PFN-Br, PFN, PFQ-Br and PFN-2TNDI; preferably made of PFN-Br;
[0008] An organic photovoltaic material light-absorbing layer, which is coated on the outside of the electron transport layer, is made of a material selected from PM6:PY-IT, PM6:PYDT-3F, PTQ10:PY-IT, PCE10:N2200, PM6:J71:PY-IT, PM6:PTQ10:PY-IT and PM6:PY-IT:PYF-IT; preferably made of PM6:PY-IT;
[0009] A hole transport layer, which is coated on the outside of the electron transport layer, and is made of a material selected from PEDOT:PSS, PTAA, poly-TPD, c-OTPD, TQ1 and P3HT; preferably made of PEDOT:PSS;
[0010] The outer electrode, which is wound around the outer side of the hole transport layer as a thin filament, is made of a material selected from a group consisting of flexible carbon nanotube spinning, silver wire, copper wire or elastic conductive fiber.
[0011] According to one embodiment of the present invention,
[0012] The organic photovoltaic material light-absorbing layer further comprises an elastomer additive, the elastomer additive being selected from SEBS, SBS, SIS, PDMS, EPDM and POE, and the amount of the elastomer additive added is 0wt%-30wt% based on the amount of the organic photovoltaic material light-absorbing layer. Preferably, the elastomer additive is SEBS, and the amount of the elastomer additive added is 0.5wt%-30wt%, more preferably 5wt% to 30wt%.
[0013] According to one embodiment of the present invention, the battery maintains more than 80% of the photoelectric conversion performance under a tensile strain of 60%.
[0014] According to one embodiment of the present invention, the battery maintains more than 80% of the photoelectric conversion performance after being repeated for more than 1000 times under a tensile strain of 30%.
[0015] The photoelectric conversion performance refers to the energy conversion efficiency.
[0016] The energy conversion efficiency is calculated by the following method: PCE = P max / P in =(V OC ×J SC ×FF) / P in The energy conversion efficiency was measured by using a solar simulator combined with a Keithley 2400 source meter instrument.
[0017] According to one embodiment of the present invention, the battery is prepared by pre-stretching by 10-100%.
[0018] According to one embodiment of the present invention, the battery is prepared by the following method:
[0019] S1) cleaning and plasma treating the elastic fiber, stretching the treated elastic fiber by 10-100%, coating the electrode layer dispersion on the treated elastic fiber, and then stopping the stretching to restore the elastic fiber to its original length, so as to obtain a fibrous inner layer stretchable electrode;
[0020] The cleaning treatment includes ultrasonic cleaning with a surfactant and a detergent;
[0021] The plasma treatment comprises treating with oxygen plasma for 10 seconds to 2 minutes;
[0022] S2) stretching the fibrous inner layer stretchable electrode by 10-100%, and coating an electron transport layer material on the fibrous inner layer stretchable electrode to obtain an electron transport layer;
[0023] S3) coating an organic photovoltaic material light absorbing layer on the electron transport layer, thereby further obtaining an organic photovoltaic material light absorbing layer;
[0024] S4) coating the hole transport layer material on the organic photovoltaic material light absorption layer to obtain a hole transport layer; then stopping the stretching to restore it to its original length;
[0025] S5) winding the outer electrode material on the hole transport layer to obtain a fully polymer stretchable fiber-shaped solar cell,
[0026] Wherein, the elastic fiber, electrode layer, electron transport layer, organic photovoltaic material light absorption layer, hole transport layer, and outer electrode are the same as those described above.
[0027] According to another aspect of the present invention, a method for preparing the above-mentioned all-polymer stretchable fibrous solar cell is provided.
[0028] According to one embodiment of the present invention,
[0029] In step S1), the diameter of the elastic fiber is 0.1-0.8 mm, the coating speed is 100-5000 mm / min, the concentration of the electrode layer dispersion is 1-20 mg / mL, and the coating is performed 1-10 times.
[0030] According to one embodiment of the present invention,
[0031] In step S2), the coating speed of the electron transport layer is 100-5000 mm / min, and the concentration of the electron transport layer material is 1-50 mg / mL;
[0032] In step S3), the coating speed of the organic photovoltaic material light absorbing layer is 100-5000 mm / min, and the concentration of the organic photovoltaic material light absorbing layer is 1-50 mg / mL;
[0033] In step S4), the coating speed of the hole transport layer is 100-5000 mm / min.
[0034] Preferably, in step S4), the hole transport layer solution is diluted to 10%-80% of the original concentration (ie, the concentration of the commercially available solution).
[0035] According to one embodiment of the present invention,
[0036] Further comprising between step S4) and step S5):
[0037] S4') annealing the fiber obtained in step S4) at 80-150° C. for 1-10 minutes.
[0038] The intrinsically stretchable fiber-shaped organic solar cell device prepared based on the technology of the present invention has a high energy conversion efficiency of up to 3.88%. The device has good tensile properties and can retain 97.3%, 95.6%, 91.8% and 85% of the initial efficiency under tensile strains of 20%, 40%, 50% and 60%, respectively. The pre-stretching strategy can increase the maximum tensile strain that the device can withstand from about 50% to about 80%. The device has good durability and stability. Under a tensile deformation of 30%, the device can still maintain more than 80% of the photoelectric conversion performance after repeated stretching for more than 1,000 times.
[0039] On this basis, 0-30wt% of the third component elastomer additive SEBS is further added to the blended solution system of the active layer to improve the tensile properties of the film and further increase the maximum tensile strain that the device can withstand to about 100%. After the introduction of SEBS, the device has better stability and can maintain higher initial photovoltaic performance after long-term placement and long-term illumination.
[0040] Beneficial Effects
[0041] The all-polymer stretchable fibrous solar cell of the present invention can further improve the mechanical stretching properties of the active layer, thereby enhancing the stretching properties of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Schematic diagram of the structure of an all-polymer intrinsically stretchable fiber-shaped solar cell device.
[0043] Figure 2 Photovoltaic performance of all-polymer intrinsically stretchable fiber-shaped solar cells.
[0044] Figure 3 The stretchable properties of intrinsically stretchable fibrous organic solar cells based on small molecule systems and all-polymer systems.
[0045] Figure 4 The cyclic stretching stability of intrinsically stretchable fibrous organic solar cells based on small molecule systems and all-polymer systems.
[0046] Figure 5 The film morphology of the active layer film with different SEBS addition amounts under 30% tensile strain.
[0047] Figure 6 In order to introduce the tensile properties of the fiber battery device of SEBS elastomer (without pre-stretching treatment), the device can withstand a tensile strain of up to 100%.
[0048] Figure 7 To improve the stability of fiber battery devices by introducing SEBS elastomer, the introduction of SEBS can enable the device to maintain higher photovoltaic performance. DETAILED DESCRIPTION
[0049] In order to enable persons with ordinary knowledge in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and the scope of the patent application. Unless otherwise specified, all technical and scientific words used in the text have the common meanings understood by those skilled in the art for the present invention. In case of conflict, the definitions in this specification shall prevail.
[0050] In the present invention, unless otherwise specified, all organic photovoltaic materials used were purchased from Nanjing Zhiyan, electrode materials such as ITO NPs and Ag NWs were purchased from J&K, PEDOT:PSS was purchased from Clevios, Heraeus, Germany, and the solar simulator used was purchased from Newport.
[0051] The terms used in this document have the following meanings:
[0052] NWs: nanowires;
[0053] NPs: nanoparticles;
[0054] ITO: Indium Tin Oxide;
[0055] PFN-Br: poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-ALT-[(9,9-di-n-octylfluorenyl-2,7-diyl)-bromide;
[0056] PM6: poly[(2,6-(4,8-bis(5-(2-ethylhexyl-3-fluoro)thiophen-2-yl)-benzo[1,2-B:4,5-B']dithiophene])-ALT-(5,5-(1',3'-di-2-thiophene-5',7'-bis(2-ethylhexyl)benzo[1',2'-C:4',5'-C']dithiophene-4,8-dione);
[0057] PY-IT: poly 2-{2-[(Z)-(10-{[(2Z)-1-(dicyanomethylidene)-3-oxyylidene-5-(thien-2-yl)-2,3-dihydro-1H-inden-2-ylidene]methyl}-12,13-bis(2-octyldodecyl)-3,9-heneicosyl[1,2,5]thiadiazolidine[4,3-e]thieno[2′,3′:4,5]thieno[3,2-b]thieno[2″,3″:4′,5′]thieno[2′,3′:4,5]pyrrolo[3,2-g]indol-2-yl)methylidene]-3-oxyylidene-2,3-dihydro-1H-inden-2-ylidene}malononitrile;
[0058] Y6: 12,13-di(2-ethylhexyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]thiadiazolo[3,4-e]thieno[2″,3″:4′,5′]thieno[2′,3′:4,5]pyrrolo[3,2-g]thieno[2′,3′:4,5]thieno[3,2-b]indole-2,10-bis(5,6-difluoro-3-(dicyanomethylidene)indene-1-one);
[0059] SEBS: styrene-ethylene / butylene-styrene block copolymer;
[0060] PEDOT:PSS: poly(3,4-ethylenedioxythiophene):polystyrene sulfonate;
[0061] Example 1: Preparation of stretchable fiber-shaped organic solar cells
[0062] (1) Configuration of each functional coating solution
[0063] Ag NWs were dispersed in ethanol solution with a dispersion concentration of 10 mg / mL; ITO NPs were dispersed in isopropanol solution with a concentration of 1 wt%, and physically dispersed before each use; PFN-Br was dissolved in methanol with a concentration of 20 mg / mL; PM6 and PY-IT were both dissolved in chloroform solvent, and the two organic semiconductor materials were mixed in a mass ratio of 1:1, with a total solution mass concentration of 12 mg / mL, and the third component SEBS elastomer was not added, that is, its addition amount was 0 wt%. The PEDOT:PSS solution was diluted to 50% of the original concentration (i.e., the concentration of the commercial solution).
[0064] (2) Preparation of intrinsically stretchable fiber substrate electrode and counter electrode
[0065] Carbon nanotube spinning or elastic conductive fiber with a diameter of 0.1 mm was used as the counter electrode. TPU polyurethane elastic fiber with a diameter of 0.5 mm was used as the core of the intrinsically stretchable fiber electrode, and ultrasonically cleaned in deionized water containing detergent, deionized water, and ethanol solution for 10 minutes, and then dried in air or nitrogen atmosphere; plasma treatment was performed on the surface of the TPU fiber to improve its wettability; the treated TPU fiber was fixed on a coating machine and a 25% tensile strain (referred to as pre-stretching) was applied; then highly conductive AgNWs and ITO NPs were uniformly coated on the surface of the TPU fiber by mechanical coating, and the coating speed was set to 1000 mm / min; the above steps could be repeated 4 times to ensure sufficient conductivity; after each coating, it was placed in a room temperature environment to dry naturally.
[0066] (3) Preparation of intrinsically stretchable fiber-shaped organic solar cells
[0067] Based on the intrinsically stretchable conductive fiber electrode prepared as described above, an intrinsically stretchable fiber battery is prepared. First, the conductive fiber base electrode is pre-stretched by 25%; a PFN-Br electron transport layer is prepared, and the electron transport layer precursor solution is uniformly coated at a speed of 1000mm / min, and the solution concentration is 20mg / mL; PM6:PY-IT:SEBS ternary organic photovoltaic material is uniformly coated at a coating speed of 5000mm / min (in this embodiment 1, the SEBS content is 0); PEDOT:PSS and other materials are used as hole transport layers, and the hole transport layer is coated at a coating speed of 1000mm / min to complete the preparation of the all-polymer FOSC working electrode; finally, a flexible carbon nanotube spinning is used as a counter electrode, and it is wound on the working electrode with a pitch of 1mm to form a biaxial device structure, such as Figure 1 shown.
[0068] Embodiment 2-6
[0069] The intrinsic stretchable fibrous organic solar cells of Examples 2-6 were prepared in the same manner as in Example 1, except that in “(1) Configuration of each functional coating solution”, the amount of SEBS elastomer was modified to 0.5wt%, 2wt%, 5wt%, 10wt% and 30wt%, respectively.
[0070] Embodiment 7-8
[0071] The intrinsic stretchable fibrous organic solar cells of Examples 7-8 were prepared in the same manner as in Example 1, except that in “(1) Configuration of each functional coating solution”, the amount of SEBS elastomer was modified to 5wt% and 30wt%, respectively, and in “(2) Preparation of intrinsic stretchable fiber substrate electrode and counter electrode”, no pre-stretching was performed.
[0072] Comparative Example 1
[0073] An intrinsically stretchable fibrous organic solar cell was prepared in the same manner as in Example 1, except that an equal amount of Y6 was used instead of PY-IT in “(1) Configuration of each functional coating solution”.
[0074] Comparative Example 2
[0075] An intrinsically stretchable fibrous organic solar cell was prepared in the same manner as in Comparative Example 1, except that in “(1) Configuration of each functional coating solution”, the amount of the SEBS elastomer was 5 wt %.
[0076] The ingredients and preparation methods of Examples 1-8 and Comparative Examples 1-2 are shown in Table 1 below.
[0077] Table 1
[0078]
[0079]
[0080] Experimental Examples
[0081] Stretchability and photovoltaic performance characterization of intrinsically stretchable fiber-shaped organic solar cells
[0082] The tensile performance test system uses a high-precision CNC slide with a fixture to characterize the tensile performance of the stretchable fiber substrate and fiber-shaped solar cells. The two ends of the fiber are fixed on two fixtures respectively. Through the program control system, the corresponding program is set to accurately measure the tensile performance under different conditions, such as single strain, multiple cycle strain, and incremental strain. The resistance change of the fiber electrode during the stretching process is characterized in real time by the Keithley 2400 digital source meter. A solar simulator (Newport, M94043A) is used to simulate AM1.5G, 100mW / cm 2 The photovoltaic performance of the cell was tested in the illumination environment and combined with the Keithley 2400 digital source meter to obtain the JV curve of the cell. Similarly, the photovoltaic test system equipped with the Keithley 2400 digital source meter was combined with the tensile performance test system to characterize the photovoltaic performance of the fiber-shaped cell in the stretching process in real time, including the JV curve and the photocurrent curve.
[0083] The intrinsic stretchable fiber organic solar cell prepared by Example 1 has excellent photovoltaic performance, and the energy conversion efficiency is as high as 3.81%. Figure 2 .
[0084] The cells prepared in Example 1 and Comparative Example 1 were tested. The prepared fiber-shaped organic solar cell has excellent photovoltaic performance under different tensile strains. Real-time detection of photocurrent changes can directly reflect the changes in the photovoltaic performance of the fiber device during continuous stretching. Within the strain range of 50%, the photocurrent of the device remains basically unchanged, while the photocurrent of the small molecule receptor system decays rapidly under 30% strain, such as Figure 3 , the device is pre-stretched by 25%.
[0085] The batteries prepared in Example 1 and Comparative Example 1 were tested. The devices have good mechanical stability. After repeated stretching for 1000 times at a tensile strain of 30%, the devices can still maintain more than 80% of the initial performance, while the small molecule system can only maintain 30% of the initial performance after 100 cycles. Figure 4 .
[0086] The film morphology of the active layer films with different SEBS addition amounts in Examples 1-6 under 30% tensile strain was tested and observed using a Zeiss scanning electron microscope. The results are shown in Figure 5 .from Figure 5 It can be seen that the further introduction of the third component SEBS improves the tensile properties of the active layer film. The tensile properties of the film with a SEBS addition of 30% are significantly improved, and the least cracks are generated under the same tensile strain (30%).
[0087] The batteries of Example 1 and Examples 7-8 were further measured. Compared with the small molecule receptor system, the introduction of SEBS can further significantly increase the maximum tensile strain that the device can withstand, and the maximum tensile strain that the device can withstand can reach 100%, such as Figure 6 shown.
[0088] The batteries prepared in Examples 1 and 4 and Comparative Examples 1 and 2 were tested. The introduction of SEBS can also improve the stability of the device and maintain higher photovoltaic performance after long-term storage in an air environment. It is applicable not only to small molecule systems but also to all-polymer systems, such as Figure 7 shown.
Claims
1. An all-polymer stretchable fiber-shaped solar cell, the cell comprising: A fibrous stretchable electrode, comprising an elastic fiber and an electrode layer coated on the elastic fiber; wherein the elastic fiber is made of a material selected from the group consisting of TPU, SBS, SEBS, SIS, PDMS, EPDM, POE, TPE, TPV, TPE, PPE and TREE, and the electrode layer is made of a material selected from the group consisting of ITO, Ag NPs, Ag NWs, Au NPs, Au NWs, Cu NWs, Cu NPs, Cu NWs, carbon nanotubes, graphene, carbon nanosheets and PEDOT:PSS; An electron transport layer, which is coated on the outside of the fibrous inner layer stretchable electrode and is made of a material selected from PFN-Br, PFN, PFQ-Br and PFN-2TNDI; An organic photovoltaic material light-absorbing layer, which is coated on the outside of the electron transport layer, and is made of a material selected from PM6:PY-IT, PM6:PYDT-3F, PTQ10:PY-IT, PCE10:N2200, PM6:J71:PY-IT, PM6:PTQ10:PY-IT and PM6:PY-IT:PYF-IT; A hole transport layer, which is coated on the outside of the electron transport layer and is made of a material selected from PEDOT:PSS, PTAA, poly-TPD, c-OTPD, TQ1 and P3HT; The outer electrode, which is wound around the outer side of the hole transport layer as a thin filament, is made of a material selected from a group consisting of flexible carbon nanotube spinning, silver wire, copper wire or elastic conductive fiber.
2. The battery according to claim 1, wherein The organic photovoltaic material light-absorbing layer further comprises an elastomer additive, which is selected from SEBS, SBS, SIS, PDMS, EPDM and POE. Based on the amount of the organic photovoltaic material in the light-absorbing layer, the amount of the elastomer additive added is 0wt%-30wt%.
3. The battery according to claim 1, wherein The battery maintains more than 80% of the photoelectric conversion performance under a tensile strain of 60%.
4. The battery according to claim 1, wherein The battery maintains more than 80% of the photoelectric conversion performance under 30% tensile strain after being repeated for more than 1000 times.
5. The battery according to claim 1, wherein The battery was prepared by pre-stretching 10-100%.
6. A method for preparing a battery according to any one of claims 1 to 5, comprising: S1) cleaning and plasma treating the elastic fiber, stretching the treated elastic fiber by 10-100%, coating the electrode layer dispersion on the treated elastic fiber, and then stopping the stretching to restore the elastic fiber to its original length, so as to obtain a fibrous stretchable electrode; The cleaning treatment includes ultrasonic cleaning with a surfactant and a detergent; The plasma treatment comprises treating with oxygen plasma for 10 seconds to 2 minutes; S2) stretching the fibrous stretchable electrode by 10-100%, and coating an electron transport layer material on the fibrous stretchable electrode to obtain an electron transport layer; S3) coating an organic photovoltaic material light absorbing layer on the electron transport layer, thereby further obtaining an organic photovoltaic material light absorbing layer; S4) coating the hole transport layer material on the organic photovoltaic material light absorption layer to obtain a hole transport layer; then stopping the stretching to restore it to its original length; S5) winding the outer electrode material on the hole transport layer to obtain a fully polymer stretchable fiber-shaped solar cell, Wherein, the elastic fiber, electrode layer, electron transport layer, organic photovoltaic material light absorption layer, hole transport layer, and outer electrode are the same as those described in claim 1.
7. The preparation method according to claim 6, wherein: In step S1), the diameter of the elastic fiber is 0.1-0.8 mm, the coating speed is 100-5000 mm / min, the concentration of the electrode layer dispersion is 1-20 mg / mL, and the coating is performed 1-10 times.
8. The preparation method according to claim 6, wherein: In step S2), the coating speed of the electron transport layer is 100-5000 mm / min, and the concentration of the electron transport layer material is 1-50 mg / mL; In step S3), the coating speed of the organic photovoltaic material light absorbing layer is 100-5000 mm / min, and the concentration of the organic photovoltaic material light absorbing layer is 1-50 mg / mL; In step S4), the coating speed of the hole transport layer is 100-5000 mm / min.
9. The preparation method according to claim 6, wherein: Further comprising between step S4) and step S5): S4') annealing the fiber obtained in step S4) at 80-150° C. for 1-10 minutes.
Citation Information
Patent Citations
Stretchable linear perovskite solar cell and preparation method thereof
CN105226192A
Flexible one-dimensional photonic crystal controlled translucent indium-free polymer solar cell
CN109119538A
High-efficiency all-polymer organic solar cell structure and preparation method thereof
CN115275020A
Intrinsic stretchable fibrous solar cell and preparation method thereof
CN115513385A
Organic photovoltaic cell and manufacturing method thereof
KR1020170113194A